Adjustment and recovery in Thailand two years after the tsunami - Bhanupong Nidhiprabha (Asian Development Bank Institute (ADBI), 2007)
This study examines Thailand's responses to the December 2004 tsunami and evaluates its reconstruction effort two years after the disaster, supplementing publicly available data with information from a field survey. Though the immediate response to the disaster can be considered a success, and much progress has been made with reconstruction, poor coordination among agencies has hampered effective and equitable delivery. Most households saw the tsunami as a 'temporary shock', and were primarily interested in house reconstruction and returning to previous occupations rather than job retraining and relocation. Credit market constraints affected the capacity of poorer households to smooth consumption. The study highlights the importance of adequate and equitable financial assistance, and the value of counseling and advice to cope with mental trauma and stress. There was no evidence that such assistance leads to aid-dependency. In contrast to Indonesia and Sri Lanka, the Thai government relied primarily on domestic sources to finance reconstruction, and construction cost escalation was not a major problem. Thailand did, however, ask developed countries for better market access for its exports, arguing that removing barriers to developed country markets is the best way of assisting developing countries hit by disasters.
Keywords: Q54; F35; H54; I38; O19; 330; Überschwemmung; Katastrophenschaden; Wirtschaftliche Anpassung; Thailand